Manajemen Program Riset Studi Kasus di MAN 2 Kudus - Khumaidah Khumaidah; Zainal Arifin; Zulkifli Syauqi Thontowi (Badan Litbang dan Diklat Kementerian Agama RI, 2022)
Based on the Decree of the Director General of Islamic Education Number 6757 of 2020 concerning the designation of madrasas as research providers, it can be analyzed that the number of madrasas designated as research madrasas is still very small compared to the number of madrasas as a whole. This study aims to describe the management of research programs at MAN 2 Kudus from the aspects of planning, organizing, implementing and evaluating. The research method used is a qualitative research method. Data was collected by means of in-depth interviews, observation and documentation. Respondents who were used as data sources were the head of the madrasa and the research mentor teacher. The results showed that the management stage of the research program includes planning, organizing, implementing and evaluating. The planning stage includes the formulation of objectives for conducting research programs and preparing human resources. The next stage is organizing which includes the formation of a research team, grouping research fields and designing a research-based curriculum. The implementation phase consists of Yourt Camp activities, Persian, teacher competency improvement, schedule preparation and mentoring process. The final stage is an evaluation carried out between the research team, the head of the madrasa and the deputy head of the madrasa to analyze the achievements of the management of the research program at MAN 2 Kudus. This research can be specified again related to research program learning techniques so that the implementation of research programs is more superior and quality so that it can increase the competitiveness of madrasa.